دراسة قياسية لأثر تقلبات أسعار النفط على الميزانية العامة في الجزائر الفترة (1990-2018). باستخدام نموذج Ecm - بوسالم, أبوبكر (جامعة الوادي - University of Eloued, 2022)
This study aims to know the effect of oil price fluctuations on the balance of the general budget in Algeria during the period ) 1992- 2019 (This is by using the ECM methodology and the study found a direct relationship between the balance of the public budget and oil prices and this is due to the Algerian economy's dependence on oil revenues in Financing the general budget.
An econometric study of the impact of oil price volatility on the public budget in Algeria during the period (1990-2018). Using ECM model
مقال
Keywords: الميزانية العامة، تقلبات أسعار النفط، الاقتصاد الجزائري، نماذج ECM